Paraphenylene Diamine Poisoning & Its Laboratory Profile: in Nawabshah, Pakistan. A Descriptive Study - Abdul Rahim Solangi, Muhammad Saleh Khaskheli, Rafia Tabassum, Aamir Raoof Memon, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2015)
Objective: This study aims to analyze the laboratory findings and the extent of damage to various tissues following the paraphenylene diamine (PPD) intoxication in Nawabshah, Pakistan. Study Design: Observational, descriptive study. Place & Duration: Department of Medicine and Intensive Care Unit (ICU), Department of Anesthesiology, Peoples University of Medical and Health Sciences Nawabshah, Pakistan during October 2013 to October 2014. Material & Methods: During October 2013 to October 2014, 178 consecutive patients were admitted to the Intensive Care Unit through Department of Medicine with history of hair dye poisoning and were included in the study. Demographic features, laboratory profile and outcomes were recorded. The biomarkers under study were complete blood count, renal profile, liver function test, creatinine phosphokinase and coagulation profile. Results: Of the 178 consecutive patients, we had 80.9% females and 19.1% males with the mean age 22±8.48 years, whose mode of intoxication was suicide (95.5%). There was no significant change for biomarkers between males and females (p-value >0.001) but we found a significant difference for laboratory marker levels of patients when compared to reference range (p-value <0.001) for all, except Prothrombin time (p-value=0.28). Conclusion: PPD poisoning has emerged as a newer trend set for committing suicide. Young females are more inclined to commit suicide through this means. It has devastating effect over various organs which is being manifested by signif cantly deranged various biomarkers.